Pembuatan Kerupuk Jagung dalam Membantu Meningkatkan Asupan Gizi Bagi Anak Stunting dan Pemanfaatan Sumber Daya Alam (SDA) Lahan Perkebunan - Muktar, Sabirul; Yulizar, Yulizar; Safitri, Aulia; Anjeli, Dini; Anggraini, Fera; Suarni, Nandar (Mitra Abdimas: Jurnal Pengabdian kepada Masyarakat, 2025)
This community service program aims to improve the nutritional intake of stunted children and pregnant women through corn cracker product innovation and to optimize the utilization of local natural resources in Pante Rakyat Village, Babah Rot District, Southwest Aceh Regency. The prevalence of stunting in the region serves as the background for implementing this program, where corn as a local commodity has the potential to become an affordable nutritious food solution. The activities were conducted using Participatory Action Research (PAR) methodology, involving 30 housewives and posyandu (integrated health post) cadres in a series of activities including: (1) observation and identification of local potential, (2) nutrition and stunting education, (3) corn cracker production training, and (4) production and distribution assistance. Results showed that 90% of participants responded positively to the program and were able to independently apply corn cracker processing technology. Nutritional content analysis revealed that the produced corn crackers contain carbohydrates (72.3%), protein (6.8%), and essential minerals such as calcium and iron that are beneficial for child growth and maternal health. Beyond health benefits, this program successfully increased active community participation in efforts to reduce stunting rates and created new entrepreneurial opportunities through the utilization of local agricultural products. Program sustainability was ensured through the establishment of a joint business group mentored by the service team. It is concluded that the development of corn cracker products contributes significantly to improving the nutritional status of stunted children and pregnant women, while promoting community economic empowerment through the utilization of local natural resources.